Perception of Exclusive Content Value and Its Influence on Social Media Users’ Interest in Subscribing - Atia Tiara Trisnawan; Adnan Kasofi; Osly Usman; Ryna Parlyna (Asosiasi Transformasi Digital Dan Bisnis Indonesia, 2026)
The growth of the creator economy has encouraged social media platforms to adopt subscription-based exclusive content as a monetization strategy. This study examines the influence of perceived exclusive content value and perceived price reasonableness on audience engagement level among social media users. Grounded in the Uses and Gratifications Theory (UGT) and the Theory of Planned Behavior (TPB), exclusive content value is conceptualized through social interaction and community, informative and content quality, status and hedonic value, and perceived price reasonableness. This research employed a quantitative explanatory approach using a survey of 128 social media users in Indonesia, analyzed through multiple linear regression with SPSS. The findings show that all examined variables positively and significantly influence audience engagement, with social interaction and community emerging as the most influential factor. These results highlight the importance of community building and fair pricing in sustaining audience engagement within the creator economy.